Text grammar: study of the text as a semantic-grammatical unit - Llanto Chávez, Lilia (2010)
The study of text as a post-sentence-level unit of the language inside the grammar of the languages is still an object which has not been well studied. The known theoretical approaches (structural and generative) have showed effectiveness in analyzing some languages (e.g. English) in the sentence level as a top projection; but communication is actually developed in post-sentencelevel units; we mean that grammar rules go beyond sentence structures. In Peru, as well as other american countries in this continent, languages have agglutinant structures, and combined syntax typology. These ones require different approaches in the strict sense of the Text Grammar. It is important to precise the difference of this approach because there are other approaches that lead us to literature analysis or, exclusively, to pragmatism.